Aviation kerosene catalyst and preparation method and application thereof
A one-pot method for preparing a Co-Ce (and/or La)-Al/SBA-15 bifunctional catalyst enhances the selectivity of aviation kerosene synthesis from syngas by achieving over 53% C8-C16 selectivity, addressing the limitations of traditional catalysts.
Patent Information
- Application Number
- CN202310752610.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-25
- Publication Date
- 2024-12-31
AI Technical Summary
Existing catalysts for synthesizing aviation kerosene from syngas suffer from low selectivity for C8-C16 components, and the development of catalysts with high dispersion and stability is needed to break the ASF distribution and enhance the selectivity of aviation kerosene production.
A one-pot method is used to prepare a Co-Ce (and/or La)-Al/SBA-15 bifunctional catalyst by adding specific ratios of triblock copolymer P123, aluminum, cerium, lanthanum, and cobalt sources, followed by crystallization, washing, and calcination, creating a catalyst with small metal particle size and high dispersion.
The catalyst achieves a C8-C16 selectivity of over 53% for aviation kerosene components, breaking the ASF distribution and improving synthesis efficiency with reduced environmental impact.
Smart Images

Figure CN119215908A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an aviation kerosene catalyst and a preparation method and application thereof, and in particular to a molecular sieve catalyst for preparing aviation kerosene from synthesis gas and a preparation method and application thereof, belonging to the technical field of aviation kerosene catalysts. Background Art
[0002] Jet fuel is one of the important fuels in the chemical industry. In the 1920s, Fischer and Tropsch developed a synthetic route for synthesizing hydrocarbons using synthesis gas as a raw material under catalysts and appropriate conditions, which is called Fischer-Tropsch synthesis. This route first prepares synthesis gas from non-petroleum resources, and then catalytically converts the synthesis gas into liquid fuel. Fischer-Tropsch synthetic fuel not only has similar performance to traditional aviation fuel, but also has low sulfur and nitrogen content in its composition, which can reduce pollution emissions from aircraft engines. This synthetic route not only has the advantages of being green and environmentally friendly, mild reaction conditions, and high atomic economy, but also has important significance for adjusting the energy structure, improving dependence on petroleum resources, and ensuring energy security.
[0003] The most notable feature of Fischer-Tropsch synthesis is the wide distribution of products (C1-C 200 The distribution of the products of the Fischer-Tropsch synthesis reaction of traditional catalysts usually follows the Anderson-Schulz-Flory (ASF) distribution law. 16 The theoretical value of the component selectivity does not exceed 40%.
[0004] It can be seen that how to break the ASF distribution of the traditional Fischer-Tropsch reaction is the key to realizing the industrialization of direct high-selectivity production of aviation kerosene from syngas. Among them, the development of catalysts in the reaction of syngas to aviation kerosene is the key to breaking the ASF distribution of the traditional Fischer-Tropsch reaction. The development of bifunctional catalysts with both metal activity and acidity is expected to break the traditional ASF distribution and concentrate the products in the C8-C 16 scope.
[0005] In addition, the synthesis of aviation kerosene from syngas is a highly exothermic reaction with water as a byproduct. Cobalt-based single metal catalysts are easily oxidized, which leads to agglomeration, sintering, and deactivation during the reaction. Therefore, the design and development of a catalyst for the direct high-selectivity synthesis of aviation kerosene from syngas with small metal particle size, high dispersion, and high stability is still a key issue that needs to be solved in the field of Fischer-Tropsch synthesis of aviation kerosene.
[0006] CN110368983A and WO2019196703A1 disclose a method for preparing a catalyst for synthesizing aviation kerosene from synthesis gas and a catalyst and its application obtained therefrom. The catalyst comprises: (A) 1 to 50% by weight of an element selected from Ru, Fe, Ni, Co, Pt, Pd as a catalytically active component, (B) 1 to 20% by weight of an element selected from the first main group metal element, transition element and lanthanide element of the periodic table different from the catalytically active component as a catalyst promoter, and (C) a carrier. When the catalyst is used for synthesizing aviation kerosene from synthesis gas, it is possible to break the ASF distribution of the traditional Fischer-Tropsch reaction, obtain a high selectivity of aviation kerosene, and in addition, an acceptable or higher CO conversion rate can be obtained. However, the preparation process of the catalyst needs to first use a weak acid and a strong base to heat-treat the carrier, and the active component and the auxiliary agent are loaded in a step-by-step impregnation manner, and the preparation process is relatively cumbersome.
[0007] CN112403491B discloses a catalyst for high-selective conversion of synthesis gas to liquid fuel, and its preparation method and application. The preparation method of the catalyst comprises the following steps: firstly, a perovskite oxide is prepared by a sol-gel method, then a certain amount of metal additive solution is added to the above perovskite oxide powder, and then the powder is fully ground and roasted, and then reduced in a hydrogen atmosphere to obtain a catalyst for high-selective conversion of synthesis gas to liquid fuel. The catalyst is used in the Fischer-Tropsch synthesis reaction, and not only has a high C5-C 20 The selectivity of the catalyst is low, and the methane selectivity is low, and the preparation method is simple. However, the patent does not study the effect of the catalyst on the C8-C 16 selectivity.
[0008] CN103468298B discloses a method for converting biomass synthesis gas into liquid fuel by Fischer-Tropsch reaction. The catalyst used in the method is a solid supported catalyst in a certain form. The main catalyst metal of the catalyst is cobalt, the carrier is a single oxide or a composite oxide, and the co-catalyst metal is selected from one or a combination of any two of Re, Ru, Cu, Mg, Zr or Pt. However, the patent does not study the effect of the catalyst on the C8-C 16 selectivity.
[0009] CN109382143B discloses a carrier and a preparation method thereof, a Fischer-Tropsch synthesis catalyst and a Fischer-Tropsch synthesis method thereof. The preparation method of the carrier comprises the following steps: (1) introducing a modification aid into a first part of a carrier precursor to obtain a modified carrier; (2) extruding the modified carrier and a second part of a carrier precursor to obtain a shaped object; (3) drying and calcining the shaped object; wherein the modification aid is selected from at least one of Group IA metal elements, Group IIA metal elements, Group IB metal elements, Group IVB-VIIIB metal elements and lanthanide elements. However, the patent also does not study the effect of the catalyst on the C8-C 16 selectivity.
[0010] Therefore, a new type of aviation kerosene catalyst and its preparation method were developed to improve C8-C 16 The selectivity of aviation kerosene components is still one of the urgent problems to be solved in this field. Summary of the invention
[0011] In order to solve the above technical problems, the purpose of the present invention is to provide an aviation kerosene catalyst and its preparation method and application. The catalyst can increase the C8-C 16 Selectivity of aviation kerosene components.
[0012] In order to achieve the above object, the first aspect of the present invention provides a method for preparing an aviation kerosene catalyst, which comprises the following steps:
[0013] (1) dissolving the triblock copolymer P123 (EO20-PO70-EO20) in an aqueous solution of an inorganic acid, stirring for a period of time to fully dissolve the triblock copolymer P123 and mix it evenly; adding an aluminum source, stirring for a period of time to fully mix it evenly; adding a cerium source and / or a lanthanum source, stirring for a period of time to fully mix it evenly; then adding a cobalt source, stirring for a period of time to fully mix it evenly; then adding a silicon source dropwise, stirring for a period of time to fully mix it evenly, to obtain a mixture;
[0014] In the mixture, the molar ratio of silicon source, aluminum source, cobalt source, cerium source and / or lanthanum source, inorganic acid, water, and triblock copolymer P123 is (50-150): (0.1-15): (1-30): (0.1-20): (50-700): (5000-39000): 1;
[0015] (2) After the mixture is subjected to a crystallization reaction, the obtained product is subjected to at least cooling, washing, solid-liquid separation, drying, and calcination to obtain the aviation kerosene catalyst.
[0016] In the above preparation method, preferably, in step (1), in the mixture, the molar ratio of silicon source, aluminum source, cobalt source, cerium source and / or lanthanum source, inorganic acid, water, and triblock copolymer P123 is (50-100): (0.1-2): (1-20): (0.1-10): (50-700): (5000-20000): 1. More preferably, in the mixture, the molar ratio of silicon source, aluminum source, cobalt source, cerium source and / or lanthanum source, inorganic acid, water, and triblock copolymer P123 is (60-70): (0.2-1.5): (5-15): (0.5-2): (100-600): (5000-20000): 1.
[0017] It should be noted that in step (1) of the above preparation method, the order of adding the aluminum source, cerium source and / or lanthanum source is not particularly limited; the aluminum source can be added first and stirred and mixed evenly, and then the cerium source and / or lanthanum source can be added; or the cerium source and / or lanthanum source can be added first and stirred and mixed evenly, and then the aluminum source can be added. However, the cobalt source needs to be added after the aluminum source and the cerium source and / or lanthanum source, and the silicon source needs to be added last.
[0018] In the above-mentioned preparation method, preferably, in step (1), the inorganic acid aqueous solution includes hydrochloric acid aqueous solution, etc. The concentration of the hydrochloric acid aqueous solution can be conventionally adjusted by those skilled in the art according to the molar ratio of each raw material defined in the present invention, for example, a 1-2 mol / L hydrochloric acid aqueous solution can be used.
[0019] In the above preparation method, preferably, in step (1), the triblock copolymer P123 is dissolved in an aqueous solution of an inorganic acid and stirred at 0-80° C. for 30-60 min. The stirring speed may be 100-500 rpm.
[0020] In the above preparation method, preferably, in step (1), the aluminum source includes one or a combination of aluminum nitrate, aluminum sulfate, aluminum chloride and aluminum isopropoxide.
[0021] In the above preparation method, preferably, in step (1), the adding of the aluminum source and stirring are carried out at 0-80° C., and the stirring time is 10-30 min.
[0022] In the above preparation method, preferably, in step (1), the cerium source includes one or a combination of cerium nitrate, cerium sulfate, cerium chloride, cerium fluoride, cerium carbonate and cerium acetate, and the lanthanum source includes one or a combination of lanthanum nitrate, lanthanum sulfate, lanthanum chloride, lanthanum oxalate and lanthanum acetate.
[0023] In the above preparation method, preferably, in step (1), the cerium source and / or lanthanum source are added and stirred at 0-80° C. for 10-30 min. The stirring speed may be 100-500 rpm.
[0024] In the above preparation method, preferably, in step (1), the cobalt source includes one or a combination of cobalt formate, cobalt acetate, ethylenediamine cobalt, cobalt citrate, potassium hexacyanocobaltate, sodium hexanitrocobaltate, hexamidocobalt chloride, bis(pentamethylcyclopentadienyl)cobalt hexafluorophosphate and ethylenediaminetetraacetic acid cobalt disodium salt.
[0025] In the above preparation method, preferably, in step (1), the addition of the cobalt source and stirring are carried out at 0-80° C., the stirring time is 30-60 min, and the stirring speed can be 100-500 rpm.
[0026] In the above preparation method, preferably, in step (1), the silicon source includes silica sol and / or tetraethyl orthosilicate, etc.
[0027] In the above preparation method, preferably, in step (1), the dropping speed of the silicon source is 1-20 mL / min, more preferably 2-10 mL / min.
[0028] In the above preparation method, preferably, in step (1), the silicon source is added dropwise and stirred at 0-80° C. for 6-24 hours. The stirring speed may be 100-500 rpm.
[0029] In the above preparation method, preferably, the temperature of the crystallization reaction is 70-150° C. and the time is 8-48 h.
[0030] In the above preparation method, preferably, in step (2), the drying temperature is 60-100° C. and the drying time is 12-24 h.
[0031] In the above preparation method, preferably, in step (2), the calcination is carried out by heating the temperature to 450-550°C at a heating rate of 2-5°C / min and then calcining for 3-12h.
[0032] In the above-mentioned preparation method, in step (2), cooling, washing and solid-liquid separation can be carried out according to conventional methods in the art, and the present invention does not impose any particular limitation on them.
[0033] A second aspect of the present invention provides an aviation kerosene catalyst, which is prepared by the above-mentioned method for preparing the aviation kerosene catalyst.
[0034] According to a specific embodiment of the present invention, preferably, the BET specific surface area of the aviation kerosene catalyst is 100-800m 2 / g, micropore volume is 0.04-0.6cm 3 / g, and the mesopore volume is 0.1-0.5cm 3 / g, and the average pore size is 2.5-30nm.
[0035] According to a specific embodiment of the present invention, preferably, the pore distribution of the aviation kerosene catalyst includes: the pore volume occupied by pores with a pore diameter of 7-20 nm is 35-55% of the total pore volume.
[0036] According to a specific embodiment of the present invention, preferably, the strong acid content of the aviation kerosene catalyst is 0.25-0.34 mmol / g, and the medium-strong acid content is 0.25-0.56 mmol / g. The strong acid content and medium-strong acid content in the catalyst can be detected by conventional methods in the art, such as using the NH3-TPD method, defining strong acid and medium-strong acid according to temperature, the medium-strong acid peak is at 250-400°C, and the strong acid peak is >400°C, and then the strong acid content and medium-strong acid content are calculated.
[0037] According to a specific embodiment of the present invention, preferably, based on the total mass of the aviation kerosene catalyst, the content of cobalt as a metal element is 5-40% (more preferably 10-25%), and the content of cerium and / or lanthanum as a metal element is 0.1-25% (more preferably 0.5-2%).
[0038] According to a specific embodiment of the present invention, preferably, the particle size of the metal particles of cobalt and cerium and / or lanthanum in the aviation kerosene catalyst is 4-10 nm, more preferably 5-8 nm.
[0039] The present invention also provides the use of the above-mentioned aviation kerosene catalyst in preparing aviation kerosene from synthesis gas.
[0040] In the above application, preferably, the reaction of preparing aviation kerosene from synthesis gas includes the following steps: mixing the aviation kerosene catalyst with quartz sand and loading it into a fixed bed reactor; introducing hydrogen into the fixed bed reactor at normal pressure and 300-500°C to reduce the aviation kerosene catalyst; and then introducing synthesis gas into the fixed bed reactor at 2-4Mpa and 180-250°C to react to obtain aviation kerosene.
[0041] In the above application, preferably, the mixing mass ratio of the aviation kerosene catalyst to quartz sand is 1:(1-2).
[0042] In the above application, preferably, the flow rate of hydrogen introduced into the fixed bed reactor is 20-100 mL / min.
[0043] In the above application, preferably, the time for introducing hydrogen into the fixed bed reactor to reduce the aviation kerosene catalyst is 4-24 hours.
[0044] In the above application, preferably, the synthesis gas comprises a mixture of H2 and CO in a molar ratio of 1-3.
[0045] In the above application, preferably, the flow rate of the synthesis gas introduced into the fixed bed reactor is 10-100 mL / min.
[0046] In the above application, preferably, the time for introducing the synthesis gas into the fixed bed reactor for reaction is 4-72 hours.
[0047] The technical solution of the present invention has at least the following beneficial technical effects:
[0048] The preparation method of the aviation kerosene catalyst of the present invention adds an aluminum source, an auxiliary metal source and a cobalt source to the synthesis system of the SBA-15 mesoporous molecular sieve, and prepares the Co-Ce (and / or La)-Al / SBA-15 bifunctional catalyst by a one-pot method. The present invention utilizes a one-pot synthesis method and a specific raw material addition sequence to allow the metal to undergo ion exchange or interaction with the strong acid center of the molecular sieve. Compared with the impregnation method, the present invention can further reduce the acid strength and strong acid amount of the catalyst, and improve the aviation kerosene C8-C 16 At the same time, the one-pot synthesis method of the present invention can reduce the increase of wastewater and pollutants in the synthesis process, significantly improve the synthesis efficiency, high atomic utilization rate, and high economic efficiency. In addition, the aviation kerosene catalyst prepared by the present invention also has the advantages of small metal particle size, high dispersion of metal particles, and regular mesoporous channel structure. The application of the aviation kerosene catalyst of the present invention to the synthesis gas to aviation kerosene reaction can break the ASF distribution of the traditional Fischer-Tropsch reaction and increase the C8-C 16 Selectivity of aviation kerosene components, C8-C 16 The selectivity of aviation kerosene components reaches more than 53%, realizing the high-selectivity synthesis of aviation kerosene products from syngas. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 This is a transmission electron microscope image of the Co-Ce-Al / SBA-15 catalyst S-1 provided in Example 1.
[0050] Figure 2 This is the small-angle X-ray diffraction spectrum of the Co-Ce-Al / SBA-15 catalyst S-1 provided in Example 1.
[0051] Figure 3This is the nitrogen adsorption / desorption curve of the Co-Ce-Al / SBA-15 catalyst S-1 provided in Example 1.
[0052] Figure 4 This is the pore size distribution curve of the Co-Ce-Al / SBA-15 catalyst S-1 provided in Example 1. DETAILED DESCRIPTION
[0053] In order to have a clearer understanding of the technical features, purposes and beneficial effects of the present invention, the technical solution of the present invention is now described in detail below, but it should not be construed as limiting the applicable scope of the present invention.
[0054] According to a specific embodiment of the present invention, preferably, the preparation method of the aviation kerosene catalyst of the present invention comprises the following steps:
[0055] (1) dissolving the triblock copolymer P123 (EO20-PO70-EO20) in a hydrochloric acid aqueous solution, and stirring at 0-80°C (preferably 40°C) for 30-60 minutes to fully dissolve the triblock copolymer P123 and mix uniformly; adding an aluminum source, and stirring at 0-80°C (preferably 40°C) for 10-30 minutes; and adding a cerium source and / or a lanthanum source, and stirring at 0-80°C (preferably 40°C) for 10-30 minutes to fully mix uniformly; then adding a cobalt source, and stirring at 0-80°C (preferably 40°C) for 30-60 minutes to fully mix uniformly; then adding a silicon source dropwise at a dropping speed of 1-20 mL / min (preferably 2-10 mL / min), and stirring at 0-80°C (preferably 40°C) for 6-24 hours to fully mix uniformly, to obtain a mixture;
[0056] In the mixture, the molar ratio of silicon source, aluminum source, cobalt source, cerium source and / or lanthanum source, inorganic acid, water, and triblock copolymer P123 is (50-150): (0.1-15): (1-30): (0.1-20): (50-700): (5000-39000): 1;
[0057] (2) The mixture is transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven at 70-150° C. for crystallization reaction for 8-48 hours, the product is taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3-5 times, and then placed in an oven at 60-100° C. for drying for 12-24 hours, and the obtained solid product is heated to 450-550° C. at a heating rate of 2-5° C. / min, and calcined for 3-12 hours to obtain the aviation kerosene catalyst Co-Ce (and / or La)-Al / SBA-15.
[0058] In the following examples and comparative examples, the catalysts were subjected to the following tests.
[0059] 1. Metal particle size detection: Use transmission electron microscopy (TEM) for detection. The instrument uses FEI TECNAI F20 transmission electron microscope. The test method is as follows: Place 1-2 mg of sample powder on the sample stage for testing.
[0060] 2. Metal content detection: small angle X-ray diffraction detection is adopted, and the instrument adopts D / MAX-2200 X-ray powder diffractometer. The method is as follows: Cu is used as the target source, and the power is 16KW.
[0061] 3. Specific surface area, pore volume, pore size and pore distribution detection: Nitrogen adsorption and desorption method is adopted, and the instrument adopts ASAP2405 physical adsorption instrument for determination. The test method is as follows: After the sample is treated, liquid N2 is used as adsorbent, the adsorption temperature is -196℃, and the analysis test is carried out; the specific surface area is calculated according to the BET method, and the pore volume, pore size and pore distribution are calculated according to the BJH method.
[0062] 4. Detection of the acidity of strong acid and medium-strong acid: NH3-TPD method is used, and the instrument is ASAP2405 physical adsorption instrument. The test method is as follows: After the sample is treated, NH3 is used as the adsorption medium to obtain the acidity of strong acid and medium-strong acid. The unit of the acidity of strong acid and medium-strong acid is mmol / g.
[0063] Comparative Example 1
[0064] This comparative example provides an aviation kerosene catalyst, which is prepared by the following steps:
[0065] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 150 mL (2 mol / L) of HCl solution and stirred for 30 min; 0.0882 g (0.432 mmol) of aluminum isopropoxide was added and stirred for 10 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 3-10 mL / min and stirred at 40°C for 24 h to obtain a mixture; the mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven at 100°C for crystallization reaction for 48 h, the product was taken out of the reactor, cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven at 100°C for drying for 12 h to obtain a solid product;
[0066] (2) 0.4342 g of cerium nitrate (1 mmol) was dissolved in 20 g of deionized water to prepare a cobalt nitrate aqueous solution, and the prepared cerium nitrate aqueous solution was added dropwise to the solid product obtained in step (1), stirred for 30 min to allow the solid and liquid to be fully mixed, allowed to stand for 12 h, and then placed in an oven at 100 ° C. for 12 h; the obtained solid product was heated to 550 ° C. at a heating rate of 3 ° C. / min, and calcined for 6 h to obtain Ce-Al / SBA-15;
[0067] (3) 1.1641 g (4 mmol) of cobalt nitrate was dissolved in 20 g of deionized water to prepare a cobalt nitrate aqueous solution, and the prepared cobalt nitrate aqueous solution was added dropwise to the Ce-Al / SBA-15 obtained in step (2) by an equal volume impregnation method, and stirred for 30 min to allow the solid and liquid to be fully mixed. The mixture was allowed to stand for 12 h, and then placed in an oven and dried at 100 ° C for 12 h; the obtained solid product was heated to 550 ° C at a heating rate of 3 ° C / min and calcined for 6 h to obtain Co-Ce-Al / SBA-15 catalyst D-1.
[0068] The Co-Ce-Al / SBA-15 catalyst D-1 of this comparative example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst D-1 was 378.20 m 2 / g, micropore volume is 0.07cm 3 / g, and the mesopore volume is 0.43cm 3 / g. The average pore size of the catalyst D-1 is 8.0nm, and the pore volume of pores with a pore size of 7-20nm accounts for 31% of the total pore volume. The XRF test results show that based on the total mass of the catalyst D-1, the content of Co (in terms of metal element) is 8.5%, and the content of Ce (in terms of metal element) is 0.3%. The NH3-TPD method measures that the strong acid content of the catalyst D-1 is 0.47mmol / g, and the medium-strong acid content is 0.20mmol / g.
[0069] Comparative Example 2
[0070] This comparative example provides an aviation kerosene catalyst, which is prepared by the following steps:
[0071] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 150 mL (2 mol / L) of HCl solution and stirred for 30 min; 0.0882 g (0.432 mmol) of aluminum isopropoxide was added and stirred for 10 min; 3.085 g (6.63 mmol) of ethylenediaminetetraacetic acid cobalt disodium salt was added and stirred for 30 min; 0.3035 g (0.931 mmol) of cerium nitrate was added and stirred for 10 min; then tetraethyl orthosilicate TEOS (9.00 g, 43.20 mmol) was added dropwise at a rate of 2-10 mL / min, and stirred at 40°C for 24 h to obtain a mixture;
[0072] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven for crystallization reaction at 100°C for 48 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven for drying at 100°C for 12 hours. The solid product was heated to 550°C at a heating rate of 2°C / min and calcined for 6 hours to obtain Co-Ce-Al / SBA-15 catalyst D-2.
[0073] The Co-Ce-Al / SBA-15 catalyst D-2 of this comparative example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst D-2 was 365.06 m 2 / g, micropore volume is 0.06cm 3 / g, and the mesopore volume is 0.34cm 3 / g. The average pore size of the catalyst D-2 is 8.8nm, and the pore volume of pores with a pore size of 7-20nm accounts for 41% of the total pore volume. The XRF test results show that based on the total mass of the catalyst D-2, the content of Co (in terms of metal element) is 18.1%, and the content of Ce (in terms of metal element) is 0.6%. The NH3-TPD method measures that the strong acid content of the catalyst D-2 is 0.35mmol / g, and the medium-strong acid content is 0.42mmol / g.
[0074] Example 1
[0075] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0076] (1) At 0°C, 4.00 g (0.69 mmol) of P123 was dissolved in 150 mL (2 mol / L) of HCl solution and stirred for 30 min; 0.0882 g (0.432 mmol) of aluminum isopropoxide was added and stirred for 10 min; 0.3035 g (0.931 mmol) of cerium nitrate was added and stirred for 10 min; then 3.085 g (6.63 mmol) of ethylenediaminetetraacetic acid cobalt disodium salt was added and stirred for 30 min; then tetraethyl orthosilicate TEOS (9.00 g, 43.20 mmol) was added dropwise at a rate of 1 mL / min and stirred at 0°C for 24 h to obtain a mixture;
[0077] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven for crystallization reaction at 150°C for 48 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven for drying at 100°C for 12 hours. The solid product was heated to 550°C at a heating rate of 2°C / min and calcined for 6 hours to obtain Co-Ce-Al / SBA-15 catalyst S-1.
[0078] The Co-Ce-Al / SBA-15 catalyst S-1 of this example was tested by transmission electron microscopy (TEM), small angle X-ray diffraction, and nitrogen adsorption and desorption. The results are as follows: Figure 1-Figure 4 shown. Figure 1 Transmission electron microscope image of the Co-Ce-Al / SBA-15 catalyst S-1 provided in this example. Figure 2 This is the small-angle X-ray diffraction spectrum of the Co-Ce-Al / SBA-15 catalyst S-1 provided in this example. Figure 3 This is the nitrogen adsorption / desorption curve of the Co-Ce-Al / SBA-15 catalyst S-1 provided in this example. Figure 4 This is the pore size distribution curve of the Co-Ce-Al / SBA-15 catalyst S-1 provided in this example.
[0079] Depend on Figure 1 It can be seen that the catalyst S-1 prepared in this example has micro / mesopores and lattice fringes, and the metal particle size of Co and Ce is about 7 nm. The metal particles are small in size and highly dispersed. Figure 2 It can be seen that the main peak at 2θ = 0.9° and the small peaks at 2θ = 1.5° and 1.8° prove that there is a highly ordered mesoporous structure in the catalyst S-1. Figure 3 It can be seen that it presents a type IV isotherm with an H1 type hysteresis loop. The specific surface area of the catalyst S-1 is 366.20 m 2 / g, micropore volume is 0.06cm 3 / g, and the mesopore volume is 0.35cm3 / g. By Figure 4 It can be seen that the average pore size of the catalyst S-1 is 9.0nm, and the pore volume of pores with a pore size of 7-20nm accounts for 46% of the total pore volume. In addition, the XRF test results show that based on the total mass of the catalyst S-1, the content of Co (in terms of metal element) is 17.8%, and the content of Ce (in terms of metal element) is 1%. The NH3-TPD method measures that the strong acid content of the catalyst S-1 is 0.32mmol / g, and the medium-strong acid content is 0.56mmol / g.
[0080] Example 2
[0081] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0082] (1) At 80°C, 4.00 g (0.69 mmol) of P123 was dissolved in 180 mL (2 mol / L) of HCl solution and stirred for 30 min; 0.0882 g (0.432 mmol) of aluminum isopropoxide was added and stirred for 10 min; 0.2294 g (0.931 mmol) of cerium chloride was added and stirred for 10 min; then 1.1737 g (6.63 mmol) of cobalt acetate was added and stirred for 30 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 20 mL / min, and stirred at 80°C for 12 h to obtain a mixture;
[0083] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven at 90°C for crystallization reaction for 24 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven at 100°C for 16 hours. The solid product was heated to 500°C at a heating rate of 5°C / min and calcined for 3 hours to obtain Co-Ce-Al / SBA-15 catalyst S-2.
[0084] The Co-Ce-Al / SBA-15 catalyst S-2 of this example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst S-2 was 379.20 m 2 / g, micropore volume is 0.07cm 3 / g, and the mesopore volume is 0.33cm 3 / g. The XRF test results show that based on the total mass of the catalyst S-2, the content of Co (calculated as a metal element) is 17.5%, and the content of Ce (calculated as a metal element) is 1.2%. The NH3-TPD method measures that the strong acid content of the catalyst S-2 is 0.33mmol / g, and the medium-strong acid content is 0.55mmol / g.
[0085] Example 3
[0086] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0087] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 200 mL (1 mol / L) of HCl solution and stirred for 60 min; 0.1216 g (0.385 mmol) of lanthanum acetate was added and stirred for 20 min; 0.1765 g (0.864 mmol) of aluminum isopropoxide was added and stirred for 20 min; then 0.988 g (6.855 mmol) of cobalt formate was added and stirred for 60 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 10 mL / min, and stirred at 40°C for 6 h to obtain a mixture;
[0088] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven for crystallization reaction at 100°C for 24 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven for drying at 100°C for 24 hours. The solid product was heated to 550°C at a heating rate of 2°C / min and calcined for 12 hours to obtain Co-La-Al / SBA-15 catalyst S-3.
[0089] The Co-La-Al / SBA-15 catalyst S-3 of this example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst S-3 was 336.10 m 2 / g, micropore volume is 0.05cm 3 / g, and the mesopore volume is 0.32cm 3 / g. The XRF test results show that based on the total mass of the catalyst S-3, the content of Co (calculated as a metal element) is 17.9%, and the content of La (calculated as a metal element) is 0.5%. The NH3-TPD method measures the strong acid content of the catalyst S-3 to be 0.32mmol / g, and the medium-strong acid content to be 0.54mmol / g.
[0090] Example 4
[0091] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0092] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 100 mL (1 mol / L) of HCl solution and stirred for 30 min; 0.184 g (0.864 mmol) of aluminum nitrate was added and stirred for 15 min; 0.4357 g (0.7698 mmol) of lanthanum sulfate was added and stirred for 15 min; then 0.988 g (6.855 mmol) of sodium hexanitrocobaltate was added and stirred for 60 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 10 mL / min, and stirred at 40°C for 16 h to obtain a mixture;
[0093] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven at 110°C for crystallization reaction for 48 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven at 100°C for 12 hours. The solid product was heated to 550°C at a heating rate of 2°C / min and calcined for 6 hours to obtain Co-La-Al / SBA-15 catalyst S-4.
[0094] The Co-La-Al / SBA-15 catalyst S-4 of this example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst S-4 was 362.30 m 2 / g, micropore volume is 0.04cm 3 / g, and the mesopore volume is 0.34cm 3 / g. The XRF test results show that based on the total mass of the catalyst S-4, the content of Co (calculated as a metal element) is 16.8%, and the content of La (calculated as a metal element) is 2%. The NH3-TPD method measures that the strong acid content of the catalyst S-4 is 0.30mmol / g, and the medium-strong acid content is 0.49mmol / g.
[0095] Example 5
[0096] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0097] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 150 mL (1 mol / L) of HCl solution and stirred for 30 min; 0.0739 g (0.216 mmol) of aluminum sulfate was added and stirred for 10 min; 0.1811 g (0.555 mmol) of cerium nitrate was added and stirred for 10 min; 1.1387 g (4.396 mmol) of cobalt acetylacetonate was added and stirred for 60 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 10 mL / min and stirred at 40°C for 16 h to obtain a mixture;
[0098] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven for crystallization reaction at 70°C for 8 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven for drying at 100°C for 12 hours. The solid product was heated to 450°C at a heating rate of 2°C / min and calcined for 6 hours to obtain Co-Ce-Al / SBA-15 catalyst S-5.
[0099] The Co-Ce-Al / SBA-15 catalyst S-5 of this example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst S-5 was 348.20 m 2 / g, micropore volume is 0.05cm 3 / g, and the mesopore volume is 0.38cm 3 / g. The XRF test results show that based on the total mass of the catalyst S-5, the content of Co (calculated as a metal element) is 10.9%, and the content of Ce (calculated as a metal element) is 0.6%. The NH3-TPD method measures the strong acid content of the catalyst S-5 to be 0.34mmol / g, and the medium-strong acid content to be 0.25mmol / g.
[0100] Example 6
[0101] This embodiment provides an aviation kerosene catalyst, which is prepared by the following steps:
[0102] (1) At 40°C, 4.00 g (0.69 mmol) of P123 was dissolved in 150 mL (1 mol / L) of HCl solution and stirred for 30 min; 0.0921 g (0.432 mmol) of aluminum isopropoxide was added and stirred for 20 min; 0.3029 g (0.932 mmol) of lanthanum nitrate was added and stirred for 20 min; then 3.542 g (8.854 mmol) of ethylenediamine cobalt was added and stirred for 30 min; then tetraethyl orthosilicate (TEOS) (9.00 g, 43.20 mmol) was added dropwise at a rate of 10 mL / min, and stirred at 40°C for 24 h to obtain a mixture;
[0103] (2) The mixture was transferred to a stainless steel reactor with a polytetrafluoroethylene liner, placed in an oven for crystallization reaction at 100°C for 48 hours, the product was taken out of the reactor and cooled to room temperature, then filtered and washed with deionized water for 3 times, and then placed in an oven for drying at 100°C for 12 hours. The solid product was heated to 550°C at a heating rate of 2°C / min and calcined for 6 hours to obtain Co-La-Al / SBA-15 catalyst S-6.
[0104] The Co-La-Al / SBA-15 catalyst S-6 of this example was subjected to nitrogen adsorption and desorption testing, XRF testing, and acid content testing. The nitrogen adsorption and desorption testing results showed that the BET specific surface area of the catalyst S-6 was 320.20 m 2 / g, micropore volume is 0.05cm 3 / g, and the mesopore volume is 0.38cm 3 / g. The XRF test results show that based on the total mass of the catalyst S-6, the content of Co (calculated as a metal element) is 21.9%, and the content of Ce (calculated as a metal element) is 1%. The NH3-TPD method measures that the strong acid content of the catalyst S-6 is 0.25mmol / g, and the medium-strong acid content is 0.50mmol / g.
[0105] Test Case
[0106] The catalysts prepared in the above comparative examples and examples were tested for their catalytic performance in producing aviation kerosene from synthesis gas.
[0107] The test includes the following steps: 0.5 g of the catalyst is mixed with 1.0 g of quartz sand, and then loaded into the middle of a fixed bed reactor with an inner diameter of 8 mm; under normal pressure and 400°C, hydrogen is introduced into the fixed bed reactor at a flow rate of 60 mL / min to reduce the catalyst for 12 hours; then, under 3 MPa and 220°C, synthesis gas (H2 to CO molar ratio of 2) is introduced into the fixed bed reactor at a flow rate of 25 mL / min and reacted for 24 hours.
[0108] The CO conversion rate and hydrocarbon product selectivity after 24 hours of reaction using different catalysts are shown in Table 1.
[0109] Table 1
[0110]
[0111] As can be seen from Table 1, Examples 1-6 of the present invention use cobalt complexes as cobalt sources, add aluminum sources, catalyst promoter metal sources and cobalt sources to the synthesis system of SBA-15 mesoporous molecular sieves, and prepare Co-Ce (and / or La)-Al / SBA-15 bifunctional catalysts by a one-pot method and a specific raw material addition sequence. Compared with the Co-Ce-Al / SBA-15 catalyst D-1 prepared by the step-by-step impregnation method in Comparative Example 1 and the Co-Ce-Al / SBA-15 catalyst D-2 prepared by changing the raw material addition sequence in Comparative Example 2, the catalyst of the present invention can break the ASF distribution of the traditional Fischer-Tropsch reaction and greatly improve the C8-C 16 Selectivity of aviation kerosene components and CO conversion.
Claims
1. A method for preparing an aviation kerosene catalyst, comprising the following steps: (1) dissolving the triblock copolymer P123 in an aqueous solution of an inorganic acid, stirring for a period of time to fully dissolve the triblock copolymer P123 and mix it evenly; adding an aluminum source, stirring for a period of time to fully mix it evenly; adding a cerium source and / or a lanthanum source, stirring for a period of time to fully mix it evenly; then adding a cobalt source, stirring for a period of time to fully mix it evenly; then adding a silicon source dropwise, stirring for a period of time to fully mix it evenly, to obtain a mixture; In the mixture, the molar ratio of silicon source, aluminum source, cobalt source, cerium source and / or lanthanum source, inorganic acid, water, and triblock copolymer P123 is (50-150): (0.1-15): (1-30): (0.1-20): (50-700): (5000-39000): 1; (2) After the mixture is subjected to a crystallization reaction, the obtained product is subjected to at least cooling, washing, solid-liquid separation, drying, and calcination to obtain the aviation kerosene catalyst.
2. The preparation method according to claim 1, wherein In step (1), the aqueous inorganic acid solution includes an aqueous hydrochloric acid solution.
3. The preparation method according to claim 1, wherein In step (1), the triblock copolymer P123 is dissolved in an aqueous solution of an inorganic acid and stirred at 0-80° C. for 30-60 min.
4. The preparation method according to claim 1, wherein In step (1), the aluminum source includes one or a combination of aluminum nitrate, aluminum sulfate, aluminum chloride and aluminum isopropoxide; Preferably, in step (1), the adding of the aluminum source and stirring are carried out at 0-80° C., and the stirring time is 10-30 min.
5. The preparation method according to claim 1, wherein In step (1), the cerium source includes one or a combination of cerium nitrate, cerium sulfate, cerium chloride, cerium fluoride, cerium carbonate and cerium acetate, and the lanthanum source includes one or a combination of lanthanum nitrate, lanthanum sulfate, lanthanum chloride, lanthanum oxalate and lanthanum acetate; Preferably, in step (1), the addition of the cerium source and / or lanthanum source and stirring are carried out at 0-80° C., and the stirring time is 10-30 min.
6. The preparation method according to claim 1, wherein In step (1), the cobalt source includes one or a combination of cobalt formate, cobalt acetate, ethylenediamine cobalt, cobalt citrate, potassium hexacyanocobaltate, sodium hexanitrocobaltate, hexamidocobalt chloride, bis(pentamethylcyclopentadienyl)cobalt hexafluorophosphate and ethylenediaminetetraacetic acid cobalt disodium salt; Preferably, in step (1), the cobalt source is added and stirred at 0-80° C., and the stirring time is 30-60 min.
7. The preparation method according to claim 1, wherein In step (1), the silicon source includes silica sol and / or tetraethyl orthosilicate; Preferably, in step (1), the silicon source is added at a rate of 1-20 mL / min; Preferably, in step (1), the silicon source is added dropwise and stirred at 0-80° C. for 6-24 h.
8. The preparation method according to claim 1, wherein In step (2), the crystallization reaction temperature is 70-150° C. and the time is 8-48 hours; Preferably, in step (2), the calcination is carried out by heating the temperature to 450-550°C at a heating rate of 2-5°C / min and then calcining for 3-12h.
9. An aviation kerosene catalyst, which is prepared by the preparation method of the aviation kerosene catalyst according to any one of claims 1 to 8; Preferably, the pore distribution of the aviation kerosene catalyst comprises: The pore volume of pores with a pore diameter of 7-20 nm accounts for 35-55% of the total pore volume; Preferably, the aviation kerosene catalyst has a strong acid content of 0.25-0.34 mmol / g, and a medium-strong acid content of 0.25-0.56 mmol / g.
10. The aviation kerosene catalyst according to claim 9, wherein: Based on the total mass of the aviation kerosene catalyst, the content of cobalt in terms of metal element is 5-40%, and the content of cerium and / or lanthanum in terms of metal element is 0.1-25%; Preferably, the particle size of the metal particles of cobalt and cerium and / or lanthanum in the aviation kerosene catalyst is 4-10 nm.
11. Use of the aviation kerosene catalyst according to claim 9 or 10 in preparing aviation kerosene from synthesis gas.
12. The use according to claim 11, wherein: The reaction of preparing aviation kerosene from synthesis gas comprises the following steps: mixing the aviation kerosene catalyst with quartz sand and loading the mixture into a fixed bed reactor; introducing hydrogen into the fixed bed reactor at normal pressure and 300-500° C. to reduce the aviation kerosene catalyst; and then introducing synthesis gas into the fixed bed reactor at 2-4 MPa and 180-250° C. to react and obtain aviation kerosene.
13. The use according to claim 11, wherein: The mixing mass ratio of the aviation kerosene catalyst to the quartz sand is 1:(1-2).
14. The use according to claim 11, wherein: The flow rate of hydrogen into the fixed bed reactor is 20-100 mL / min; Preferably, the time for introducing hydrogen into the fixed bed reactor to reduce the aviation kerosene catalyst is 4-24 hours.
15. The use according to claim 11, wherein: The synthesis gas comprises a mixture of H2 and CO in a molar ratio of 1-3; Preferably, the flow rate of the synthesis gas introduced into the fixed bed reactor is 10-100 mL / min; Preferably, the synthesis gas is introduced into the fixed bed reactor for a reaction time of 4-72 hours.
Citation Information
Cited By
Preparation method of tin-based perovskite thin film
CN122054896A